Dampak Pemberian MP-ASI Dini dengan Kejadian Diare Pada Bayi di Rumah Sakit Paru dr. Ario Wirawan Salatiga - Listianingsih Listianingsih; Tri Sakti Widyaningsih (Jurnal Persada Husada Indonesia, 2023)
Diarrhea is a major cause of morbidity and mortality in children less than 5 years. The infant age group is the group with high levels of diarrhea. Early complementary feeding (MP-ASI) can cause digestive disorders such as diarrhea. This type of research is a quantitative study with a descriptive correlative design using a cross sectional approach. The total population of 23 respondents, when the Slovin calculation was carried out, the number of respondents was 23, the inclusion criteria in this study were infants aged 0-24 months and mothers / fathers who were available to be respondents. The research instrument is a questionnaire. The data obtained were analyzed using the Spearman rank test.Early complementary complementary breastfeeding to infants at Lung Hospital dr. Ario Wirawan Salatiga aged <6 months were 16 respondents (69.6%) while those who provided complementary breastfeeding according to age or ≥6 months were 7 respondents (30.4 %). The incidence of diarrhea in infants at the Lung Hospital Dr. Ario Wirawan Salatiga who experienced acute diarrhea was 15 respondents (65.2%) and those who experienced chronic diarrhea were 8 respondents (34.8%). The conclusion of this study: there is a relationship between early complementary breastfeeding and the incidence of diarrhea in infants at Dr. Ario Wirawan's Lung Hospital, Salatiga (p value = 0.005).